2017
DOI: 10.1128/aac.00468-17
|View full text |Cite
|
Sign up to set email alerts
|

Gepotidacin (GSK2140944) In Vitro Activity against Gram-Positive and Gram-Negative Bacteria

Abstract: Gepotidacin is a first-in-class, novel triazaacenaphthylene antibiotic that inhibits bacterial DNA replication and has in vitro activity against susceptible and drug-resistant pathogens. Reference in vitro methods were used to investigate the MICs and minimum bactericidal concentrations (MBCs) of gepotidacin and comparator agents for Staphylococcus aureus, Streptococcus pneumoniae, and Escherichia coli. Gepotidacin in vitro activity was also evaluated by using time-kill kinetics and broth microdilution checker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 9 publications
6
59
0
1
Order By: Relevance
“…[331] Nafithromycin (WCK-4873) is aketolide in which the original carbamate is replaced by alactone moiety. [330,332] It is currently under investigation in phase II studies for community-acquired bacterial pneumonia (CABP) by Wockhardt. Its in vitro activities are comparable to telithromycin, with advantages against some ketolideresistant Pneumococci.…”
Section: Tetracyclinesmentioning
confidence: 99%
“…[331] Nafithromycin (WCK-4873) is aketolide in which the original carbamate is replaced by alactone moiety. [330,332] It is currently under investigation in phase II studies for community-acquired bacterial pneumonia (CABP) by Wockhardt. Its in vitro activities are comparable to telithromycin, with advantages against some ketolideresistant Pneumococci.…”
Section: Tetracyclinesmentioning
confidence: 99%
“…Gepotidacin (GSK2140944) is a triazaacenaphthylene bacterial type II topoisomerase inhibitor with a novel mode of action with in vitro activity against most target pathogens resistant to established antibacterials (12)(13)(14)(15). Phase 2 studies have demonstrated the efficacy of gepotidacin in acute bacterial skin and skin structure infections and uncomplicated urogenital gonorrhea (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Gepotidacin is currently also being developed for uncomplicated UTIs. Its MICs against fluoroquinolone susceptible E. coli are much higher than for levofloxacin, but cross resistance to fluoroquinolones has not been described yet in E. coli 111,112 .…”
Section: Beyond Old Classes New Chemical Scaffolds New Targets or Bimentioning
confidence: 99%